Association between neutropenia and death rate of bacterial neonatal sepsis - Elly Noer Rochmah; Ekawaty Lutfia Haksari; Sri Mulatsih (Indonesian Pediatric Society, 2008)
Background Neonatal sepsis remains a crucial problem with highmorbidity and mortality. Not less than four million neonates dieevery year, 99% of which occur in developing countries withinfection as the main cause (36%) of death. The prognosticfactors of bacterial neonatal sepsis vary. However the death ratein neonatal sepsis with neutropenia is suspected to be higher thanthat in non-neutropenic condition.Objectives The purpose of this study was to identify whetherneutropenia would increase the death risk of bacterial neonatalsepsis.Methods We conducted a retrospective cohort study. Subjectswere neonates at Instalasi Maternal Perinatal (IMP) of Dr. SardjitoHospital in Yogyakarta who met the eligibility criteria. Duringthe five-year period Qanuary 2002- January 2007), out of 1821cases of suspected neonatal sepsis, 365 (16.7%) were found tohave bacterial cause in the culture of body's fluid (blood, urine,and cerebrospinal). Out of these 16.7% patients suffering fromneutropenia, 39.6% patients died, whereas 9.1 o/o patients weresurvive [RR 4.72, (95% CI: 2.49 to 8.93), P < 0.01].Conclusion Neonates suffering bacterial sepsis with neutropeniahad death risk 4.7 times higher than those who did not haveneutropenia.